The impact of multiple blended binders on the properties and performance of concrete pavement - Putra Jaya, Ramadhansyah (2015)
The effects of multiple blended binders on the properties and performance of concrete pavement are investigated in this study. Mineral admixtures, namely, silica fume (SF), metakaolin (MK) and rice husk ash (RHA), are used to replace ordinary Portland cement (OPC) at replacement levels of 0% (control mix), 5%, 10%, and 15% by mass-to-mass basis. The performances of the multiple binders on the concrete pavement properties were evaluated based on compressive strength, flexure strength, density, and porosity. Test results showed that the mineral admixtures can be satisfactorily used as cement replacement materials in order to increase the properties of pavement concrete. Moreover, concrete pavement with 5% and 10% replacement levels showed excellent performance with good strength and low porosity.